The Existence of Pancasila Values and its Threats in the Digital Space of the Millenial Generation - Yunas, Novy Setia (Journal of Civics and Moral Studies, 2024)
Globalization has changed many things in people's lives, from fundamental transformations in mindsets to social interaction models and changes in the social, political, and economic order. Now, the development of globalization certainly does not stand alone; it goes hand in hand with current phenomena such as the Industrial Revolution 4.0, technological disruption, and society 5.0, as well as the influence of the COVID-19 pandemic that has hit the world since 2020. This reality has led to the rapid development of technology, information, communication, and media. Social media is one of the essential markers of the rapid growth and change. The presence of social media is very ambivalent for human life; on the one hand, the presence of social media will provide convenience and flexibility in building communication without knowing barriers and boundaries. On the other hand, social media also holds many problems, such as the phenomenon of filter bubbles and echo chambers. This is a severe problem for the nation amidst the threat of radicalism, intolerance, and terrorism. After all, the filter bubble and echo chamber phenomenon on social media will be an instrument for developing these ideologies, especially since our millennial generation is the largest social media user today. Through a literature review, this paper leads us to reflect that one way to counter the threat of filter bubbles and echo chambers on social media is to return to the values of Pancasila. Strengthening and revitalizing the values of Pancasila is very important both in the real world and in cyberspace through the application of competence in interpreting the values of Pancasila in the digital space, producing and sharing content related to the values of Pancasila, and the most crucial is to actively collaborate in developing the values of Pancasila and Unity in Diversity in the digital space of our millennial generation.